Understanding SARS‐CoV‐2 endocytosis for COVID‐19 drug repurposing - Glebov, Oleg O. (FEBS J, 2020)
The quest for the effective treatment against coronavirus disease 2019 pneumonia caused by the severe acute respiratory syndrome (SARS)‐coronavirus 2(CoV‐2) coronavirus is hampered by the lack of knowledge concerning the basic cell biology of the infection. Given that most viruses use endocytosis to enter the host cell, mechanistic investigation of SARS‐CoV‐2 infection needs to consider the diversity of endocytic pathways available for SARS‐CoV‐2 entry in the human lung epithelium. Taking advantage of the well‐established methodology of membrane trafficking studies, this research direction allows for the rapid characterisation of the key cell biological mechanism(s) responsible for SARS‐CoV‐2 infection. Furthermore, 11 clinically approved generic drugs are identified as potential candidates for repurposing as blockers of several potential routes for SARS‐CoV‐2 endocytosis. More broadly, the paradigm of targeting a fundamental aspect of human cell biology to protect against infection may be advantageous in the context of future pandemic outbreaks.